Empowering Diabetes Management through Nutritional Innovations: The Role of Golden Rice Cookies Enriched with Piper crocatum Extract - Setyawati, Andina; Jafar, Nuurhidayat; Trisasmita, Laksmi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Diabetes mellitus (DM) is a growing global health issue, with dietary management posing significant challenges for patients. The habit of consuming high-sugar and high-fat snacks, as observed at Bajeng Community Health Center, Gowa Regency, increases the risk of serious complications, including diabetic ulcers and cardiovascular diseases. This program aimed to develop and optimize Golden Rice Cookies, a healthy snack enriched with locally sourced Piper crocatum extract, as a nutritional alternative for DM patients. A participatory approach was employed, involving an initial analysis of partner conditions, product development through organoleptic and hedonic testing, and education on diabetes dietary management. Over three months, patients consumed Golden Rice Cookies, and outcomes were evaluated based on fasting blood glucose (FBG), body mass index (BMI), and dietary compliance levels. The results demonstrated that Golden Rice Cookies were well-received, with high satisfaction scores for taste, aroma, and texture (≥4 on a 5-point scale). Regular consumption significantly reduced FBG by an average of 29.9 mg/dL, BMI by 1.3 kg/m², and increased dietary compliance by 20.5%. The flavonoids and polyphenols in P. crocatum contributed to oxidative stress suppression, inflammation reduction, and modulation of key biomarkers such as MMP-9 and NGAL. This program successfully empowered DM patients to manage their condition through a sustainable and locally based nutritional innovation. This approach holds promise for replication in other regions with high diabetes prevalence to support more effective and sustainable diabetes management.